Sailor Moon R [videorecording (DVD)] : the movie - Takeuchi, Naoko (Viz Media, 2017)
Long before Mamoru found his destiny with Usagi, he gave a single rose in thanks to a lonely boy who helped him recover from the crash that claimed his parents. This long-forgotten friend, Fiore, has been searching the galaxy for a flower worthy of that sweet gesture long ago. The mysterious flower he finds is beautiful, but has a dark side- it has the power to take over planets! To make matters worse, the strange plant is tied to an ominous new asteroid near Earth!